Evaluation of growth performance of juvenile African catfish [Clarias gariepinus (Burchell, 1822)] fed with striped catfish [Pangasius hypophthalmus (Sauvage, 1878)] viscera and putative probiotic isolate - Abu Bakar, Siti Nadia (2018)
Post-harvest processing of fresh striped catfish (Pangasius hypophthalmus) has resulted in large volume of waste by-products such as viscera. Since it is not consumed by humans, utilization of discarded fish parts especially viscera may protect environment from the risk of disposal-related health problems and environmental pollution. Current research focus on the efficacy of utilizing discarded striped catfish (Pangasius hypophthalmus) viscera as feed ingredient to improve the growth and survival of juvenile African catfish (Clarias gariepinus). The discarded viscera were dried at 105oC prior for nutrient content identification. The proximate analysis of P. hypophthalmus dried viscera shows that it contains 16.37 ± 0.81% of crude protein, 48.1 ± 10.77% crude lipid, 67.53 ± 1.86% of moisture and 0.2 ± 0.06% of ash respectively.The indigenous putative probiont in the viscera were isolated and analysed based on its physiological and biochemical properties, adhesiveness, antibacterial activity and identified molecularly. The selected probiont were identified molecularly as Weisella confusa strain and possessed an outstanding performance from the identification of properties in the laboratory. It was found out to grow excellence in temperature ranged from 25 oC to 35 oC, salinity 0% until 3.5%, multiplied at pH 4, 6, 8 and 10, able tolerate to 0.15% and 0.30% presence of bile salts as well as possessed a good adhesive ability. Furthermore, current isolates shows a high inhibition zone towards some aquatic pathogenic bacteria tested; Aeromonas hydrophila, Streptococcus agalactiae, Vibrio harveyi and Vibrio parahaemolyticus. The isolates also were found resistant to Vancomycin (30 μg) and Amoxilin (10 μg) while susceptible to Streptomycin (10 μg), Vancomycin (5 μg) and Ampicilin (10 μg) antibiotic disk. The suitability of dried fish viscera as feed ingredient in African catfish (initial size 2.71 ± 0.14 gm) were tested through feeding diet according to three different inclusion levels (10%, 20% and 30%) and it was found out that feed contained 20% of dried viscera yielded highest growth rate thus chosen for next feeding trial experiment. The efficacy of probionts isolate as well as dried viscera were tested to juveniles African catfish in 40 days of feeding trial according to four treatments; (T1) Commercial feed; (T2) Mix of commercial feed with dried viscera (T3) Mix of commercial feed with putative probiont isolated (T4) Mix of commercial feed with dried viscera and isolated probiont. Findings from feeding trial proven that T3 shows significantly high growth performance (P<0.05) in term of body weight, body weight gain, average daily gain and specific growth rate in compare to T1 but exhibited no significant difference (P<0.05) with T2 and T4. Feed intake and feed conversion ratio were not significantly difference (P>0.05) among all treatment but numerical value presented show high feed intake in group of fish fed probiotic T3. Survival rate of all experimental fishes were not significant difference (P>0.05) affected each other but relatively highest in T2 followed by T3, T4 and numerically lowest in T1. Further haematological assessment carried out proven that T3 shows better performance (P<0.05) in term of haemoglobin concentration, mean corpuscular volume and white blood cell count in compare with other treatment. Histological assessment made on intestinal epithelium height of villi between four treatments also proven that T3 shows significantly longer length (P<0.05) of villi in compare to T1, T2 and T4. Hence, African catfish diet composed of 20% P. hypophthalmus dried viscera or composed of putative probiont suspension from P. hypophthalmus mid-gut intestine at dosage of 109 cfu/ml diet was recommended to promote Clarias gariepinus growth performance.